STRATEGI PUBLIC RELATIONS PT HONDA MEGATAMA KAPUK DALAM CUSTOMER RELATIONS - horidatul bakiyah (Universitas Bina Sarana Informatika, 2020)
The development of information and communication technology is increasingly growing. Today's society is so spoiled by the many types of communication media, and one of the most interesting people in Indonesia today is Instagram social media. Many positive things can be explored from Instagram, and one of the most used by people in Indonesia is as a medium for doing business online. Many of the offline-based companies are now using Instagram to show the existence of their companies in the world of social media. Likewise with PT. Honda Megatama Kapuk participated in utilizing Instagram as a strategy in customer relations. PT. Honda Megatama Kapuk itself is a company engaged in the automotive sector. The research was conducted with qualitative research methods, where the technique of collecting data through the stages of observation, in-depth interviews, literature studies and documentation. The results show that the strategy of using Instagram social media in Customer Relations is very effective in reaching customers who are active in social media, making it easier for companies to disseminate information about products and company operations. Through Instagram, customers feel more familiar and close to the company so that it has a positive impact on the company in monitoring what information needs are needed by loyal customers.Keywords: Public Relations Strategy, Customer Relations, Instagram